Microneurographic research in women - Fu, Qi (Frontiers in Physiology, 2012)
This article reviews microneurograpic research on sympathetic neural control in women under both physiological and pathophysiological conditions across the lifespan. Specifically, the effects of sex, age, race, the menstrual cycle, oral contraceptives, estrogen replacement therapy, and normal pregnancy on neural control of blood pressure in healthy women are reviewed. In addition, sympathetic neural activity during neurally mediated (pre)syncope, the Postural Orthostatic Tachycardia Syndrome, obesity, the Polycystic Ovary Syndrome, gestational hypertension and preeclampsia, chronic essential hypertension, heart failure, and myocardial infarction in women are also reviewed briefly. It is suggested that microneurographic studies provide valuable information regarding autonomic circulatory control in women of different ages and in most cases, excessive sympathetic activation is associated with specific medical conditions regardless of age and sex. In some situations, sympathetic inhibition or withdrawal may be the underlying mechanism. Information gained from previous and recent microneurographic studies has significant clinical implications in women’s health, and in some cases could be used to guide therapy if more widely available.